2018
DOI: 10.1111/febs.14661
|View full text |Cite
|
Sign up to set email alerts
|

Autocyclized and oxidized forms ofSCR7 induce cancer cell death by inhibiting nonhomologousDNAend joining in a LigaseIVdependent manner

Abstract: Nonhomologous DNA end joining (NHEJ) is the major DNA double-strand break (DSB) repair pathway in mammals. Previously, we have described a small molecule inhibitor, SCR7, which can inhibit NHEJ in a Ligase IV-dependent manner. Administration of SCR7 within the cells resulted in the accumulation of DNA breaks, cell death, and inhibition of tumor growth in mice. In the present study, we report that parental SCR7, which is unstable, can be autocyclized into a stable form. Both parental SCR7 and cyclized SCR7 poss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
37
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 44 publications
(40 citation statements)
references
References 70 publications
(151 reference statements)
3
37
0
Order By: Relevance
“…In our previous study, we have reported that SCR7 can improve the effect of radiation in mice tumor and cancer cell lines. 17,18 In this study, SCR130 used in combination with radiation showed elevated levels of 53BP1 and γH2AX foci in cancer cells. This was further confirmed using neutral comet assay.…”
Section: Discussionmentioning
confidence: 57%
See 3 more Smart Citations
“…In our previous study, we have reported that SCR7 can improve the effect of radiation in mice tumor and cancer cell lines. 17,18 In this study, SCR130 used in combination with radiation showed elevated levels of 53BP1 and γH2AX foci in cancer cells. This was further confirmed using neutral comet assay.…”
Section: Discussionmentioning
confidence: 57%
“…Among that, SCR130 exhibited 20-fold better cytotoxicity as compared with SCR7. 17,18 Moreover, SCR130 specifically inhibited Ligase IV-mediated joining with no effect on Ligase I activity. Although at equivalent concentrations SCR130 was insensitive to Ligase III-mediated joining, it showed an effect at four-fold higher concentration (data not shown).…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…To further improve HDR e ciency, we tested two different small-molecule compounds, Scr7 and L755507. Scr7 is a speci c DNA ligase IV inhibitor that can improve HDR e ciency by inhibiting the nonhomologous endjoining (NHEJ) pathway [26], and L-755507 is a selective β3 adrenergic receptor partial agonist that enhances CRISPR-mediated HDR e ciency [21]. Two of these small-molecule compounds have been proven to improve the HDR ratio in mammalian cells, mouse embryonic stem cells and pluripotent stem cells in other studies [22,27].…”
Section: Discussionmentioning
confidence: 99%